Pertanggungjawaban Hukum Marketplace di Indonesia terkait Pelanggaran Hak Cipta: Tantangan, Regulasi, dan Upaya Pencegahan dalam Era E-Commerce - Djamaludin, Samsul; Fuad, Fokky (LPPM Universitas Ekasakti Padang, 2024)
Marketplace legal liability in Indonesia regarding copyright infringement in the E-Commerce era faces increasing complexity and a rise in copyright infringement cases. The formulation of the problem in this research is the complexity of the problem of copyright infringement in the market, as well as obstacles in demanding market accountability, the role of the market, and what preventive measures need to be strengthened to overcome this problem. This research combines normative and empirical perspectives to understand the crucial aspects of market legal accountability. The research results show the need for revisions in the legal framework regarding market legal responsibility for copyright infringement in Indonesia. The inconsistency between Article 15 of the ITE Law and Article 10 of the Copyright Law creates obstacles in implementing the rules. Therefore, concrete measures are needed to harmonize regulations and improve copyright protection in the market.